EFEKTIVITAS PENGGUNAAN CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN CUSTOMER LOYALTY - Utami, Desinta Handini (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
ABSTRACT : Customer Relationship Management (CRM) is one ofthe means to establish sustainable relationships between stakeholdersand shareholdernya. Today many companies are using CRM tobuild relationships with customers. By utilizing CRM, companieswill know what is expected and required customers sehinggan willcreate an emotional bond that is capable of creating a close businessrelationship and open and two-way communication between them.CRM is necessary to begin to be created, built, and implemented incompanies engaged in various fields of business. CRM is applied canaffect the increase in customer loyalty. By utilizing CRM, companieswill know what is expected and required customers sehinggan willcreate an emotional bond that is capable of creating a close businessrelationship and open and two-way communication between them.Thus the customer loyalty can be maintained and not easily switchto other products and brand.Key words: Customer Relationship Management, CustomerLoyalty